Intra- and interspecific variation in tooth morphology of Procyon cancrivorus and P. lotor (Carnivora, Procyonidae), and its bearing on the taxonomy of fossil South American procyonids - Rodríguez, Sergio G. (2016)
The family Procyonidae (raccoons, coatis, olingos, ringtails, kinkajous, and their extinct relatives) consists of six extant genera and is restricted to North and South America. Currently recognized fossil species suggest that procyonid diversity was previously much greater, including six extinct genera throughout South America. However, it is unusual that so many confamilial taxa are represented in a relatively brief span of time and restricted geographic region, and, considering that six of ten are based on badly preserved specimens, often fragments of bone with worn teeth, the validity of many of these taxa is suspect. As a step towards reevaluating past procyonid diversity in South America, we sought to identify the degree of intra- and interspecific variation in six molariform teeth of extant Procyon, particularly to identify which teeth are potentially most useful for identifying fossil procyonids. The six molariform cheek teeth analyzed consistently yielded smaller intra- than interspecific variation, permitting high accuracy of taxonomic classification. However, this accuracy varied by tooth, and the upper and lower first molars proved to be the most reliable. Thus, these particular teeth should be preferred, if available, as bases for recognizing extinct species of procyonids or reevaluating currently recognized extinct species, as a means to prevent nomina dubia.